The Essential Role of Financial Statements in Evaluating Financial Performance - Bakkara, Ardewifna; Ningsih, Bella Setya; Putri, Nabilla (Universitas Islam Negeri Sumatera Utara, 2024)
The purpose of this study is to examine the significance of financial statements in evaluating a company's performance. The research provides benefits for the company by offering insights into the importance of financial reports in assessing performance and making future decisions. This study also benefits researchers in understanding how critical these financial statements are for performance evaluation. The research employs a naturalistic approach, which is commonly known as a qualitative method. This approach is used to examine natural phenomena, where researchers play a key role. The study uses qualitative data, which consists of information in the form of words, sentences, or diagrams and pictures. The data source for this research comes from secondary data, meaning it is derived from existing written studies, notes, and books. Financial performance is a reflection of the financial condition of a company during a certain period, in terms of both capital raising and distribution, which are typically measured by capital adequacy indicators, liquidity, and profitability. The benefits of performance evaluation for management include overseeing organizational operations, assisting in decision-making, identifying employee training and development needs, providing feedback to employees on how their performance is valued, and serving as a basis for reward distribution.